Green Disclosure Mediates Good Corporate Governance and Social Performance on Budgeting Effectiveness in the Basic Materials Sector - Rahmawati; H. Dini Arifian; Furniawan Furniawan (JURNAL ECONOMINA, 2026)
In addition to examining the mediating role of green disclosure, this study also examines how social performance and good corporate governance (GCG) influence green disclosure and budgeting effectiveness (ROA). Using secondary data from companies listed on the Indonesia Stock Exchange (IDX) and analyzed using Eviews 12, this study takes a quantitative approach. The results show that social performance and GCG have no effect on green disclosure, and GCG has no effect on budgeting efficiency. On the other hand, although green disclosure has no effect and is unable to mediate the relationship between the variables, social performance has a positive impact on ROA. These results confirm that environmental disclosure is still not a primary factor in determining financial performance. Therefore, businesses must integrate sustainability.